An Automated Step-Wise Micro-Compression Device for 3D Dynamic Image-Guided Failure Assessment of Bone Tissue on a Microstructural Level Using Time-Lapsed Tomography - Levchuk, Alina; Schneider, Philipp; Meier, Matias; Vogel, Peter; Donaldson, Finn; Müller, Ralph (Frontiers in Materials, 2018)
Microstructural bone phenotypes, such as the intracortical canal network, could be directly linked to the mechanical failure behavior of cortical bone tissue. In addition, high accumulation of microdamage can significantly increase bone brittleness and thus, is a precursor of mechanical failure. Here, we discuss the development and validation of an automated step-wise micro-compression device (MCD) for dynamic image-guided failure assessment (DIGFA) of intracortical bone microstructure and bone microdamage. The device was found to be highly accurate and precise with positioning errors of less than 1 µm and force errors of less than 1.25 N. In addition, the results of a first biological study using DIGFA and time-lapsed computed tomography are presented. In short, whole mouse femora from mature C57BL/6 (B6) and C3H/He (C3H) mice with mid-diaphyseal notches were tested in step-wise compression and concomitantly imaged until failure. DIGFA was performed at the TOMCAT beamline of the Swiss Light Source using synchrotron radiation-based computed tomography (SR CT). Following the experiment, intracortical porosity was separated into the canal network, osteocyte lacunae, and microcracks for subsequent morphometric evaluation. The thicker cortex of C3H was penetrated by a dense canal network, whereas in B6 only a few scattered canals were observed. For B6, the first occurrence of crack was noted at 1.45% local strain, while for C3H, crack initiation took place only at 2.66% local strain. In addition, we were able to relate whole bone mechanics to local failure events by deriving correlations between microstructural porosity and microdamage propagation. In conclusion, initiation and accumulation of microcracks were investigated for two mouse phenotypes demonstrating that DIGFA in combination with SR CT is a suitable technique for time-lapsed three-dimensional assessment of bone morphology and bone fracture behavior down to the cellular level.